2021
DOI: 10.3389/fcell.2021.736677
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of miRNAs Profiles in Serum of Patients With Steatosis and Steatohepatitis

Abstract: Non-alcoholic fatty liver disease (NAFLD) is emerging as one of the most common chronic liver diseases worldwide, affecting 25% of the world population. In recent years, there has been increasing evidence for the involvement of microRNAs in the epigenetic regulation of genes taking part in the development of steatosis and steatohepatitis—two main stages of NAFLD pathogenesis. In the present study, miRNA profiles were studied in groups of patients with steatosis and steatohepatitis to compare the characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 89 publications
0
21
0
Order By: Relevance
“…Finally, a serum microRNA (miRNA) profile revealed the potential relationship between different miRNAs and the presence of steatosis or steatohepatitis in 16 patients. It was reported that miR-374a-5p, miR-1-3p, and miR-23a-3p do not target genes that are directly involved in the pathogenesis of MAFLD [78]. On the other hand, the specific roles of some miRNAs are still unknown.…”
Section: Epigenetic Reprogrammingmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a serum microRNA (miRNA) profile revealed the potential relationship between different miRNAs and the presence of steatosis or steatohepatitis in 16 patients. It was reported that miR-374a-5p, miR-1-3p, and miR-23a-3p do not target genes that are directly involved in the pathogenesis of MAFLD [78]. On the other hand, the specific roles of some miRNAs are still unknown.…”
Section: Epigenetic Reprogrammingmentioning
confidence: 99%
“…It has been considered a therapeutic target, given that its inhibition of the L/R-type pyruvate kinase (PKLR) could lead to a decrease in de novo lipogenesis (DNL) and oxidative phosphorylation in mitochondria, having a positive effect in the early stages of MAFLD. However, this particular miRNA was also found to inhibit the AMPK complex, thus contributing to progression to steatohepatitis as well as suppressing tumor necrosis factor (TNF) and Fas cell surface death receptor (FAS), possibly contributing to fibrosis and establishment of HCC [78].…”
Section: Epigenetic Reprogrammingmentioning
confidence: 99%
“…miRNAs and long non-coding RNAs (lncRNAs) are highly confirmed to play a crucial role in mediating the progression of diseases, including NASH. An altered hepatic miRNA profile has been shown in NASH in both human and animal models [ 35 , 36 ] and more evidence demonstrated the role of miRNAs in liver functions [ 37 ]. Concerning lncRNAs, their role in inflammation-related diseases, especially NASH, was mentioned in detail in a recent review by Shabgah et al, [ 38 ] who presented multiple examples of NAFLD-related lncRNAs and their potential mechanisms contributing to disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of some of the miRNAs selected after our regression modeling and biological fine-tuning was reinforced by previous studies searching for miRNA biomarkers. Thus, miR-23a-3p and miR-19a-3p were found to be deregulated (with an opposite trend) in the serum of patients with NASH [ 22 ]. Similarly, miR-19a and b were both upregulated in the serum of simple steatosis NAFLD patients [ 23 ], whereas in a different study, miR-30a-3p was also substantially upregulated in NAFLD patients, and its suppression attenuated hepatic steatosis in HepG2 cells [ 24 ].…”
Section: Discussionmentioning
confidence: 99%